The Effect of Breast Milk Storage Container on the Amount of Probiotic Microbiota in Breast Milk - Pasalina, Putri Engla; Amran, Vitri Yuli Afni; Devita, Hendri (International Health Sciences Journal, 2024)
Developing babies require important bacteria from breast milk, which impact gut microbiota in adulthood and lifelong health. Breast milk also contains hundreds to thousands of different microbiomes. These microbiomes prevent infection, inflammation, organ growth, healthy microbial colonization, and aid immune maturation. The type of storage container material used influences bacterial colonization of breast milk. The aim of this study was to analyze the effect of storage containers on breast milk probiotic microbiota. The type of research is a true experiment with a pretest and posttest control group design. The probiotic microbiota studied is Lactic Acid Bacteria (LAB). The examination of the total colonization of lactic acid bacteria was carried out using the Quebec Colony Counter Unit. Data were analyzed by paired sampleT-test. The results showed that the average number of Lactic Acid Bacteria colonies stored in glass bottle is greater than the number of LAB colonies stored in plastic bag (95x106 CFU/ml vs 77x106 CFU/ml). However, statistical tests showed no significant difference between the number of BAL colonies of breast milk stored in plastic bags and breast milk stored in glass bottles.